Making Digital Marketing Strategies in the Hotel Industry: Case Study of Implementation of New Wave Marketing on Budget Hotel - Indra Perdana Wibisono (Indonesian Journal Of Business And Economics, 2019)
The marketing strategy carried out in the era of new wave marketing will cause the old paradigm related to marketing to be abandoned. Marketing strategies through New Wave Marketing are currently being used and developing rapidly. New Wave Marketing connects producers with customers on a human-to-human basis supported by machine-to-machine described through 12C. This study aims to determine the New Wave Marketing at a Budget Hotel. This research uses descriptive research with a qualitative approach. The informants of this research are the Hotel Capsule Owners and Managers. The data analysis techniques used in this study are domain and taxonomic analysis. The results showed that there were eleven components of the New Wave Marketing Strategy in Capsule Hotels. Online and offline strategies are also carried out by Capsule Hotels.